2013
DOI: 10.3390/ma6093755
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Magnetic Targeting Anti-Tumor Drug Delivery System: Cytosine Arabinoside-Loaded Bacterial Magnetosome

Abstract: Abstract:To ease the side effects triggered by cytosine arabinoside (Ara-C) for acute leukemia treatment, a novel magnetic targeting anti-tumor drug delivery system was constructed through bacterial magnetosomes (BMs) from Magnetospirillum magneticum AMB-1 combined with Ara-C by crosslinking of genipin (GP). The results showed that Ara-C could be bonded onto the membrane surface of BMs effectively through chemical crosslinking induced by dual hand reagents GP. The average diameters of BMs and Ara-C-coupled BMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…Compared with previous studies, [16][17][18] these findings suggested that Ara-C might attach to the PLGA on the BM lipid membrane. The zeta potentials of the BMs and ABMs-P were -28.8±7.6 mV and -30.5±6.6 mV, respectively, which indicated that both the BMs and ABMs-P were stable and could distribute well in the next drug release experiment.…”
mentioning
confidence: 41%
See 1 more Smart Citation
“…Compared with previous studies, [16][17][18] these findings suggested that Ara-C might attach to the PLGA on the BM lipid membrane. The zeta potentials of the BMs and ABMs-P were -28.8±7.6 mV and -30.5±6.6 mV, respectively, which indicated that both the BMs and ABMs-P were stable and could distribute well in the next drug release experiment.…”
mentioning
confidence: 41%
“…16 Because of the potential toxicity of glutaraldehyde, we have successfully prepared a BM drug delivery system that relies on genipin (GP), instead of glutaraldehyde, for crosslinking. 17,18 GP is isolated from the fruit of the gardenia plant and has conspicuous therapeutic effects that are antitumor, antithrombus, anti-inflammation, and antidiabetes. In considering the effect of PLGA in this study, we tried to combine GP and PLGA as dual cross-linkers to increase the binding sites of Ara-C.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetite magnetosomes have also been used to detect single-nucleotide polymorphism based on a fluorescence resonance energy transfer technique in which double-stranded labeled DNA synthesized by polymerase chain reaction (PCR) and immobilized to the magnetosomes hybridizes to target DNA and a fluorescence signal is detected (Maruyama et al 2004;Nakayama et al 2003;Ota et al 2003;Tanaka et al 2003;Yoshino et al 2003). Magnetosomes, when conjugated to other molecules, have been used as sensors for Staphylococcus enterotoxin B in milk (Wu et al 2013) and for the simultaneous detection of the drugs Pefloxacin and Microcystin-LR in seafood (Sun et al 2013).…”
Section: Applications Of Magnetotactic Bacteria and Magnetosomes In Nmentioning
confidence: 99%
“…"Nanobodies," functional antibody fragments, have been coupled in vivo to magnetosomes via genetic fusion (Pollithy et al 2011). Conjugated magnetic nanoparticles such as these can also be coupled to drugs or genes which could then be used as carriers of these molecules for targeted therapy of tumors (Chertok et al 2007;Deng et al 2013;Guo et al 2012a;Sun et al 2007;Zhao et al 2010) or as vaccine delivery systems (Tang et al 2012a).…”
Section: Applications Of Magnetotactic Bacteria and Magnetosomes In Nmentioning
confidence: 99%
“…These are composed of iron oxide or iron sulfide minerals enveloped by lipid membrane rich in amino groups [18,19]. In addition, previous literatures have evidenced that BMs are used to deliver various therapeutic agents such as drugs [20,21], enzyme [22], and DNA [23]. In a case, the activity of glucose oxidase immobilized BMs is 40 times effective than those immobilized on artificial magnetite particles [24].…”
Section: Introductionmentioning
confidence: 99%